John 8.17—An Invitation to Perjury?. Issue 1 (April 2017) - Förster, Hans
The traditional translation of the Greek word ἀληθής as "true" or "accepted as fact" in John 8.17 appears to suggest a legal stipulation which would pose serious legal problems if used in judicial proceedings. This raises the question whether the translation is true to the mark. The paper suggests that ἀληθής might have a slightly different meaning in John 8.17 and should be translated as "trustworthy."